Leptin Expression and Gene Methylation Patterns in Alcohol-Dependent Patients with Ethyltoxic Cirrhosis—Normalization After Liver Transplantation and Implications for Future Research. - Proskynitopoulos, P J; Rhein, M; Jäckel, E; Manns, M P; Frieling, H; Bleich, S; Thum, T; Hillemacher, T; Glahn, A (Alcohol & Alcoholism, 2018)
Aims Liver transplantation is the only curative treatment available for patients with end-stage alcoholic liver disease. As different studies showed a significant association between leptin plasma levels, gene methylation patterns and the extent of craving in alcohol-dependent patients, we investigated the effect of liver transplantation on leptin expression and promoter methylation. Short Summary The present study shows that in alcohol-dependent patients with liver cirrhosis leptin is significantly higher before liver transplantation and decreases significantly after transplantation. Alcohol-dependent patients on the waiting list had significantly higher leptin promoter methylation values than patients who underwent liver transplantation for other reasons than alcoholic liver disease. Methods Only plasma of 118 and peripheral blood mononuclear cells of 121 patients were used: healthy controls (C, n = 24/22), alcohol-dependent patients without ethyltoxic liver cirrhosis (AD, n = 24/22), patients after liver transplantation for other reasons than ethyltoxic liver cirrhosis (C-Tx, n = 18/21), alcohol-dependent patients suffering from ethyltoxic liver cirrhosis on the transplantation waiting list (Pre-Tx, n = 30/28) and patients with prior ethyltoxic liver cirrhosis after liver transplantation (Post-Tx, n = 22/28). Results Leptin protein was significantly elevated in the pre-transplantation cohort when compared to post-transplantation and alcohol-dependent cohorts. Furthermore, leptin promoter methylation was higher in ethyltoxic patients before transplantation compared to non-ethyltoxic patients after transplantation, but not when compared to ethyltoxic patients after transplantation. C-Tx had lower methylation values than all other groups except for Post-Tx. Conclusions Our study outlines the role of leptin protein levels as a marker for AD-related liver damage, contrasting it from AD without severe liver damage. With regard to the results of the methylation analysis, inflammation of the liver appears to cause mechanisms of leptin regulation to deviate from transcriptional regulation. Our data also suggest that leptin regulation is altered in ethyltoxic liver disease when compared to liver cirrhosis caused by other pathologies.